Chronic alcohol-induced dysbiosis of the gut microbiota and gut metabolites impairs sperm quality in mice - Li, Hui; Li, Ningshan; Lu, Qudong; Yang, Jun; Zhao, Jiang; Zhu, Qiong; Yi, Shanhong; Fu, Weihua; Luo, Tingting; Tang, Jiawei; Zhang, Yi; Yang, Guoliang; et al. (Frontiers in Microbiology, 2022)
Studies have indicated that the ethanol exposure impairs the gut microbiota, At the same time, high levels of alcohol exposure damage sperm in mice. This study aimed to assess the effect of chronic alcohol consumption on intestinal microbiota in mice and analyse the potential pathophysiological effect of altered intestinal microbiota on sperm quality. We established a mouse model of chronic alcohol consumption by allowing male C57 mice to freely ingest 10% ethanol for 10 weeks, and collected the faecal microbiota of the male mice in the chronic drinking group (alcohol) and the control group (control) and transplanted the specimens into the transplant groups (the alcohol-faecal microbiota transplantation [FMT] group and the control-FMT group). Sperm quality was significantly decreased in the alcohol-FMT group compared with the control-FMT group. Gut microbiota analysis revealed that the abundance of 11 operational taxonomic units (OTUs) was altered in the alcohol-FMT group. Nontargeted metabolomics identified 105 differentially altered metabolites, which were mainly annotated to amino acids, lipids, glycerophosphoethanolamine, organic oxygenic compounds, organic acids and their derivatives, steroids, and flavonoids. In particular, the oxidative phosphorylation pathway, which is the key to spermatogenesis, was significantly enriched in the alcohol-FMT group. Moreover, compared with the control-FMT group, the alcohol-FMT group presented significantly higher serum endotoxin and inflammatory cytokine levels, with more pronounced T cell and macrophage infiltration in the intestinal lamina propria and elevated levels of testicular inflammatory cytokines. In addition, RNA sequencing showed significant differences in the expression of testis-related genes between the alcohol-FMT group and the control-FMT group. In particular, the expression of genes involved in gamete meiosis, testicular mitochondrial function, and the cell division cycle was significantly reduced in alcohol-FMT mice. In conclusion, these findings indicated that intestinal dysbiosis induced by chronic alcohol consumption may be an important factor contributing to impaired sperm quality. Chronic alcohol consumption induces intestinal dysbiosis, which then leads to metabolic disorders, elevated serum endotoxin and inflammatory cytokine levels, testicular inflammation, abnormal expression of related genes, and ultimately, impaired sperm quality. These findings are potentially useful for the treatment of male infertility.